Fluid And Electrolyte Status In Diarrhoeic Conditions Of Dogs - Jabina Martha Philip (Department of Clinical Medicine, College of Veterinary and Animal Sciences, 2003)
The study "Fluid and electrolyte status in diarrhoeic conditions of dogs" was conducted in the Department of Clinical Medicine during the period of one and a half years from June 2001 to October 2002, to evaluate plasma volume and electrolyte status, haemogram and the possible etiological factors in diarrhoeic dogs. Detailed investigations of twenty clinical cases and six healthy normal cases were done after making a tentative diagnosis based on history. Blood and faecal samples were collected on the day of admission to the hospital. Detailed laboratory examination of faecal samples, blood and microbiological studies were carried out. Haematological parameters were estimated as described by Schalm et af. (1975). Biochemical analyses were done under standard conditions of operation as described, using photometer 5110 (Boehringer Mannheim). Plasma volume was determined as per the protein precipitation and extraction method of Hunsaker (1965). Ancylostomes was identified as the major parasitic cause for diarrhoea. Though bacteria could be isolated from all the cases, it could not give a true reflection of the actual disease. A low HA titre was obtained for the canine parvoviral infection. Haemogram revealed a significantly lower value for haemoglobin. Biochemical analysis revealed reduced sodium and bicarbonate level indicative of their excess loss through faeces. Significantly lower level of plasma protein